Health on equal terms? - Västra Götaland, 2009 - Health on equal terms, Västra Götaland - 2009 - Public Health Agency of Sweden (City of Gothenburg, 2015)
The survey “Health on equal terms?” is a national survey, conducted every year since 2004. The Public Health Agency is responsible for the survey and Statistics Sweden (SCB) is responsible for the distribution, collection and registration. During the data collection in 2009, the City of Gothenburg ordered an additional sample for Gothenburg.

The additional sample in 2009 included all individuals aged 16-84 years living in Gothenburg. The questionnaire were answered by 2,098 individuals from the sample in Gothenburg, representing a response rate of 50 percent.

Including the national sample produced by Statistics Sweden (SCB), a total of 3,332 individuals participated from Västra Götaland County.

The questionnaire consisted a total of 135 questions covering e.g. issues of health, lifestyle, economic conditions, work and employment, and security and social relations. In addition to data collected through the questionnaires, registry data were also included.

Purpose:

The aim of the national survey was to investigate the health in the population and to show changes in the population's health over time as a follow up of the national health politics. The aim of the additional sample in Gothenburg was to investigate the health in the population living in Gothenburg.

Undersökningen ”Hälsa på lika villkor?” är en stor nationell undersökning som genomförts varje år sedan 2004. Folkhälsomyndigheten ansvarar för undersökningen medan Statistiska centralbyrån (SCB) ansvarar för utskick, insamling och registrering av svar. I samband med undersökningen 2009 beställde Göteborgs Stad ett tilläggsurval för Göteborg.

Tilläggsurvalet för 2009 års undersökning inkluderade samtliga invånare 16-84 år i Göteborg. Frågeformuläret besvarades av totalt 2098 individer från tilläggsurvalet, vilket motsvarade en svarsfrekvens på 50 procent.

Antal svar för hela Västra Götalands län, d.v.s inklusive det nationella urvalet som tagits fram av Statistiska Centralbyrån (SCB), uppgick till totalt 3332 individer.

Frågeblanketten bestod av 77 numrerade frågor varav flera hade delfrågor, vilket genererade totalt 135 frågor. Frågorna handlade bl.a. om hälsa, levnadsvanor, ekonomiska förhållanden, arbete och sysselsättning samt trygghet och sociala relationer. Förutom variabler som samlats in via frågeblanketten har ett antal registervariabler hämtats från SCB:s Registret över totalbefolkningen (RTB), utbildningsregistret, inkomst- och taxeringsregistret och Geodatabasen.

Syfte:

Syftet med den nationella undersökningen var att ta reda på hur Sveriges befolkning mår och lever. Syftet med urvalet för Göteborgs Stad var att ta reda på hur befolkningen i Göteborgs Stad mår och lever.
Hälsa på lika villkor? - Västra Götaland, 2009 - Hälsa på lika villkor, Västra Götaland - 2009
Keywords: Health Services; Hälso- och sjukvård; Physical Examination; Hälsokontroll; Dental Care; Tandvård; Hearing; Hörsel; Life Style; Livsstil; Medicine; Medicin; Exercise; Träning; Population Surveillance; Populationsövervakning; Hearing Loss; Hörselnedsättning; Socioeconomic Factors; Socioekonomiska faktorer; Tinnitus; Öronsusning; Urinary Incontinence; Urininkontinens; Anxiety; Ångest; Overweight; Övervikt; Diet; Kost; Alcohol Drinking; Alkoholkonsumtion; Work; Arbete; Asthma; Astma; Diabetes Mellitus; Diabetes; Eczema; Eksem; Public Health; Folkhälsa; Leisure Activities; Fritidsaktiviteter; Cardiovascular Diseases; Kardiovaskulära sjukdomar; Headache; Huvudvärk; Health; Hälsa; Health Status; Hälsotillstånd; Hypertension; Högt blodtryck; Body Weight; Kroppsvikt; Drug Utilization; Läkemedelsförsörjning; Gastrointestinal Diseases; Mag-tarmsjukdomar; Migraine Disorders; Migränsjukdomar; Oral Health; Munhälsa; Depression; Depression; Interpersonal Relations; Mellanmänskliga relationer; Mental Health; Psykisk hälsa; Registries; Register; Smoking; Rökning; Disease; Sjukdom; Pain; Smärta; Tobacco, Smokeless; Rökfri tobak; Social Support; Socialt stöd; Stress, Psychological; Psykologisk stress; Vision, Ocular; Syn; Sleep; Sömn; Sleep Wake Disorders; Sömn- och vakenhetsstörningar; Fatigue; Trötthet; Occupations; Yrken; Occupational Exposure; Yrkesmässig exponering; Hypersensitivity; Överkänslighet; Feeding Behavior; Ätbeteende